(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The electronic commerce has become an integral part of the global economy during the last decade. The most obvious indication of the importance of electronic commerce in the world economy is rapidly increasing Internet use in trade and other sectors. The successful growth of E-commerce promotes the use of other electronic media, as well as it is perspective for development of territories located in backcountry and remote regions. In the result of the Internet and electronic commerce technological development there can be observed changes also in the business environment. In these circumstances successful strategies applied in different levels and sectors for the implementation of the most modern information technology achievements, as well as for the development of professionals with appropriate knowledge, expertise and skills, are becoming increasingly important for the development of electronic commerce in Latvia. The article will view the current situation, will explain the main limiting factors and advantages for successful development of the electronic commerce in Latvia.